(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
In light of globalization and internationalization of financial markets, issues arising from financial crises have become increasingly serious and fundamental, creating a lot of debate among experts around the world. So, many studies have attempted to investigate what measures can be taken to detect and prevent crises before they devastate the economies. Therefore, this paper examines the Effectiveness of the Fiscal Policy (FP) to Avoid, Reduce or Treat the Financial Crisis in Malaysia. Scholars have yet to agree on the issue concerning the appropriate fiscal measures, particularly with respect to the question of whether or not fiscal policies are more effective tool in dealing with financial crisis. Majority of comprehensive theoretical frameworks are fragmented. Somehow, this framework has been tested in developed countries. Only very few studies were conducted in developing nations. The results of this research provide empirical support for the extended model. Moreover, this work has added to the understanding of Fiscal Policy (FP) to Avoid, Reduce or Treat the Financial Crisis in Malaysia, also with theories research.